Effect of Amine Additive for the Synthesis of Cadmium Selenide Quantum Dots in a Microreactor. Issue 2 (11th September 2015) - Jeong, Da‐Woon; Swain, Basudev; Seong, Tae‐Yeon; Park, Kyoung‐Tae; Lee, Chan Gi; Kim, Bum Sung
Abstract : The effect of octylamine flow rate on the structure and morphology of CdSe quantum dots synthesized in a microreactor was studied. The flow rate of octylamine was varied from 0.005 ml/min to 0.030 ml/min, and the optical properties of the synthesized particles were analyzed by UV–vis and photoluminescence spectroscopy. The particle size of the quantum dots was found to increase with an increasing octylamine flow rate. Further, UV–vis and photoluminescence bands were found to be red‐shifted with an increasing flow rate. We determined that, by controlling octylamine flow rate, the particle size of the quantum dots could be controlled. This method will help to determine the optimal octylamine flow conditions for synthesizing nanoparticles for use in a diverse range of applications.